RNA-Sequencing Analysis of the Spleen and Gill of Takifugu rubripes in Response to Vibrio harveyi Infection - Gao, Dongxu; Lei, Wei; Wang, Chenshi; Ni, Ping; Cui, Xiaoyu; Huang, Xindi; Ye, Shigen (Frontiers in Veterinary Science, 2022)
Takifugu rubripes is commonly subjected to the disease-causing bacterium, Vibrio harveyi. However, the mechanism involved in the immune response of T. rubripes to V. harveyi infection is unclear. We conducted a transcriptomic analysis of the spleen and gill from T. rubripes infected with V. harveyi. We obtained 60,981,357 and 60,760,550 clean reads from the control and infected spleens, and 57,407,586 and 57,536,651 clean reads from the control and infected gills, respectively. We also identified 1,560 and 1,213 differentially expressed genes in the spleen and gill, respectively. Gene ontology analysis revealed that the most enriched biological process in both the spleen and gill was “immune response”. The most enriched Kyoto Encyclopedia of Genes and Genomes immune response-related pathways were the NOD-like receptor signaling pathway in the spleen and cytokine-cytokine receptor interaction in the gill. We found ten candidate immune-related genes in the spleen and gill. These putative immune pathways and candidate genes will provide insight into the immune response mechanisms of T. rubripes against V. harveyi.